Keeping busy learners informed: email is most useful for medical residents! - Karwowska, Anna; Tse, Sandy (Revue canadienne de l’éducation médicale, 2019)
Background: Educators need to ensure trainees have access to the rotation orientation information they need in the most effective way possible. We wanted to find the best method to distribute this information. Methods: We provided post-graduate medical trainees rotating through the Pediatric Emergency Medicine program at the Children’s Hospital of Eastern Ontario in Ottawa, Canada, the regular rotation information package three ways: email, online, and paper. We surveyed them to find out which method(s) they used and which they found most useful. Results: All traineeswere able to access the electronic orientation package via email and most found this method useful. Most also found the paper package distributed at the orientation helpful. Few accessed the online wiki site. Conclusion: Using email is efficient and effective and can save both the time and cost of producing paper packages. The wiki site was not used frequently in our cohort, but may be worth future exploration.